2000
DOI: 10.2175/193864700784607695
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nitrifier Growth Rates in NYC Water Pollution Control Plants

Abstract: New York City DEP in collaboration with the City College of New York has developed a step-feed BNR process that has demonstrated significant nitrogen removal. The process is being considered for implementation at several water pollution control plants. Several bench scale and pilot studies have been initiated to develop design criteria for step-feed BNR. In this paper the methods used to measure maximum specific nitrifier growth rate, µ A and nitrifier decay rate, b A are presented. Sequencing batch reactors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…The linearized results, shown in Figure 7 , resulted in an average decay rate of 0.27 d -1 . This decay rate is higher than previously measured for ammonia oxidizers (Fillos, 2000;Katehis 2001) typically in the range of 0.09 to 0.15 d -1 .…”
Section: Process Developmentcontrasting
confidence: 60%
See 2 more Smart Citations
“…The linearized results, shown in Figure 7 , resulted in an average decay rate of 0.27 d -1 . This decay rate is higher than previously measured for ammonia oxidizers (Fillos, 2000;Katehis 2001) typically in the range of 0.09 to 0.15 d -1 .…”
Section: Process Developmentcontrasting
confidence: 60%
“…The tank at that time was producing significant levels of nitrates (~50% of the total NO X -N produced). The protocol for measurement of ammonia oxidizer decay that was described by Fillos (2000) was used, with the exception that the substrate was nitrite (KNO 2 ) instead of ammonia. The pH in the primary decay reactor was held at 8.0 (±0.05) by a combination of a 2mM phosphate buffer, and an automated NaOH dispensing system operating on a pH feedback loop (Omega Engineering, USA).…”
Section: Process Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, consisting of laboratory experiments or ASM1 sensitivity analysis, have shown that the following default parameter values proposed in the original ASM1 publication needed to be reconsidered (Henze et al, 1987): N The decay rate (b A ) of the autotrophic biomass, which defines the fraction of nitrifying bacteria that is lost each day by death or predation under endogenous conditions, was found to be systematically too low. New values obtained from recent specific batch experiments for various secondary sludge at 20uC fall between 0.17 and 0.19 d 21 (Dold et al, 2005;Fillos et al, 2000;Lopez et al, 2006;Marrs et al, 2004;Stensel et al, 2002). The original default values ranged from 0.04 to 0.15 d 21 at 20uC (Henze et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Performance of the step feed basin was compared with that of an existing plug flow aeration basin of identical size. A significant volume of literature has been devoted to step feed and its applications in recent years, including work by Fillos et al (2000), Carrio et al (2000), and Crawford et al (2000). However, much of this recent work is based on "standalone" step feed systems.…”
Section: Methodsmentioning
confidence: 99%